Dialogues, Reinterpretations, Critical Repositionings in Literary and Cultural Discourses of 21st Century Canada - Branach-Kallas, Anna; Drewniak, Dagmara (Studia Anglica Posnaniensia, 2020)
Dialogues, Reinterpretations, Critical Repositionings in Literary and Cultural Discourses of 21st Century Canada